Re-Materialisasi Epistemologi Sains: Dinamika Embodied Cognition dan Fluid Creativity Melalui Intervensi Haptik Berbasis ISA - Jessy Parmawati Atmaja; I Wayan Lasmawan; Desak Putu Parmiti (SENTRI: Jurnal Riset Ilmiah, 2026)
This research addresses the cognitive crisis in primary science education caused by "digital reductionism," which frequently triggers disembodied learning. Excessive reliance on static screen simulations has led to a disconnect between a student’s cognitive processes and physical reality. This study aims to mitigate this gap through a re-materialization strategy, utilizing the frameworks of Material Engagement Theory (MET) and Embodied Cognition. The primary objective is to evaluate the effectiveness of haptic intervention implemented through a Cognitive Interactive Pop-Up Book integrated with an Inquiry Science Approach (ISA). A mixed-methods research design with an Exploratory Sequential approach was employed, involving 60 fifth-grade students. Quantitative data were analyzed using MANCOVA to assess the intervention's impact on dependent variables simultaneously. The results indicate a highly significant difference between the experimental and control groups. The experimental group’s post-test HOTS score reached 82.5, significantly outperforming the control group’s 65.0. Similarly, in Fluid Creativity, the experimental group achieved 78.4 compared to the control group’s 58.2 (p < .001). Specifically, the haptic group showed sharp increases in high-level cognitive indicators: Analysis (Gain 38.6) and Evaluation (Gain 36.4), with a substantial Effect Size of 0.42 (Partial Eta Squared). These findings empirically confirm that physical re-materialization serves as a "cognitive prosthetic," bridging the gap between abstract concepts and physical reality through sensorimotor feedback. This study concludes that activating the hands as "thinking senses" is crucial for developing embodied knowledge and adaptive creativity in primary education.